2011
DOI: 10.1111/j.1745-4514.2011.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

SCREENING OF ENZYMATIC ACTIVITIES IN NON-SACCHAROMYCESCIDER YEASTS

Abstract: The activities of polygalacturonase, pectin lyase, β‐glucosidase, β‐xylosidase and protease were determined using solid media in 420 wild non‐Saccharomyces cider strains identified by internal transcribed spacer‐restriction fragment length polymorphism. The identified species corresponded to Hanseniaspora valbyensis, Hanseniaspora uvarum, Hanseniaspora osmophila, Metschnikowia pulcherrima, Candida parapsilosis and Pichia guilliermondii. The most common activity exhibited was that of β‐glucosidase (33%), with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Hanseniaspora uvarum (anamorph Kloeckera apiculata ) is an apiculate yeast species frequently found on mature fruits (Spencer et al, 1992 ; Morais et al, 1995 ) and particularly on grapes where it forms part of the grape and fermentation microbiome.Its association with grapes and the first stages of alcoholic fermentation (AF) has been reported repeatedly during the last century (Castelli, 1955 ; Schütz and Gafner, 1993 ; Hierro et al, 2006 ) and for most—if not all—vineyard regions worldwide (Heard and Fleet, 1985 ; Holloway et al, 1990 ; Mateo et al, 1991 ; Comi et al, 2001 ; Beltran et al, 2002 ; Jolly et al, 2003 ; Combina et al, 2005 ; Li et al, 2010 ; Zott et al, 2010 ; Kachalkin et al, 2015 ). H. uvarum is also frequently isolated from other fermented beverages such as cider (Lachance, 1995 ; Cabranes et al, 1997 ; Valles et al, 2007 ; Pando Bedrinana et al, 2012 ), palm wine and cashew juice (Owuama and Saunders, 1990 ), tequila (Bilbao et al, 1997 ), sugar-cane aguardente (Morais et al, 1997 ), etc. It is part of the natural microbiome of many fermented food processes, including coffee (Masoud et al, 2004 ) and cocoa (Batista et al, 2015 ) fermentations.…”
Section: Introductionmentioning
confidence: 99%
“…Hanseniaspora uvarum (anamorph Kloeckera apiculata ) is an apiculate yeast species frequently found on mature fruits (Spencer et al, 1992 ; Morais et al, 1995 ) and particularly on grapes where it forms part of the grape and fermentation microbiome.Its association with grapes and the first stages of alcoholic fermentation (AF) has been reported repeatedly during the last century (Castelli, 1955 ; Schütz and Gafner, 1993 ; Hierro et al, 2006 ) and for most—if not all—vineyard regions worldwide (Heard and Fleet, 1985 ; Holloway et al, 1990 ; Mateo et al, 1991 ; Comi et al, 2001 ; Beltran et al, 2002 ; Jolly et al, 2003 ; Combina et al, 2005 ; Li et al, 2010 ; Zott et al, 2010 ; Kachalkin et al, 2015 ). H. uvarum is also frequently isolated from other fermented beverages such as cider (Lachance, 1995 ; Cabranes et al, 1997 ; Valles et al, 2007 ; Pando Bedrinana et al, 2012 ), palm wine and cashew juice (Owuama and Saunders, 1990 ), tequila (Bilbao et al, 1997 ), sugar-cane aguardente (Morais et al, 1997 ), etc. It is part of the natural microbiome of many fermented food processes, including coffee (Masoud et al, 2004 ) and cocoa (Batista et al, 2015 ) fermentations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the β‐glucosidase was not detected in T. delbrueckii HB02, HB03, HC04, and HG01, S. bacillaris HA01 and HB07, and D. hansenii HC01, which may be due to the differences between species or the lack of a complex growth medium and the fastidious nature of the organisms. Furthermore, it have been previously reported that the ability of wine yeasts to produce β‐xylosidase was very rare and was currently only found in the genera Hanseniaspora , Pichia Metschnikowia , Torulaspora, and Candida (Bedriñana et al, ; Bokulich et al, ; Manzanares, Ramón, & Querol, ; Mateo et al, ). Interestingly, the β‐xylosidase activity was detected in D. hansenii HB08 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The release of volatile aroma is related to hydrolytic enzymes secreted by non-Saccharomyces yeasts, with β-glucosidase, β-xylosidase, and pectinase having outstanding contributions (Belda et al, 2016;Canonico, Agarbati, Comitini, & Ciani, 2015;Comitini et al, 2011;López et al, 2015). In previous studies, strains in the genera Candida, Debaryomyces, Hanseniaspora, Metschnikowia, and Torulaspora were found to secrete β-glucosidase (Bedriñana et al, 2012;Fernández, Ubeda, & Briones, 2000;Iranzo, Otero, & Brionesperez, 2010;Mateo et al, 2011). However, in the same species, strains produced different enzymatic activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Saccharomyces genus is not considered as a good producer of exogenous enzymes. Instead, several non-Saccharomyces yeast species exhibit natural enzymatic activities [91]. The enzymes of interest produced by these yeasts include esterases, lipases, glycosidases, proteases, and cellulases usually related to hydrolysis of structural components [4,92].…”
Section: Biotechnological Application Of Extracellular Enzymes Secretmentioning
confidence: 99%